Suppressing Dissolution of Pt‐Based Electrocatalysts through the Electronic Metal–Support Interaction. Issue 38 (26th August 2021) - Lin, Gaoxin; Ju, Qiangjian; Jin, Yan; Qi, Xiaohuan; Liu, Weijing; Huang, Fuqiang; Wang, Jiacheng
Abstract: Suppressing the Pt dissolution still remains a big challenge in improving the long‐term stability of Pt‐based catalysts in electrochemical energy conversion. In this work, the degradation of Pt nanoparticles is successfully suppressed via weakening the Pt–O dipole effect by adjusting the electronic structure of surface Pt atoms. The specially designed graphitic‐N‐doped carbon nanosheets with balanced N content and graphitization degree as well as fewer defects are prepared for anchoring Pt nanoparticles to enhance the electronic metal–support interaction. This can accelerate the electron transfer from Pt to substrate, decrease the surface electron density of Pt, and attenuate the Pt–O interaction. As a result, the rate of Pt dissolution decreases by 95% compared to that of commercial Pt/C toward the oxygen reduction reaction and thus the catalytic stability is significantly improved in the electrochemical accelerated durability test. The theoretical simulation shows that the inhibition of surface Pt dissolution is attributed to the enhanced energy barrier in the initial relaxation process. Abstract : The dissolution of Pt from an electrocatalyst is significantly suppressed via the electronic metal–support interaction between Pt and graphitic‐N‐doped carbon. The electron transfer from Pt to substrate can decrease the electron density of surface Pt, and thus weaken the dipole effect between Pt and O2 . As a result, the stability of the catalyst is significantly enhanced.